2018
DOI: 10.1186/s12881-017-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between BDNF Val66Met polymorphism and emotional symptoms after mild traumatic brain injury

Abstract: BackgroundBrain-derived neurotrophic factor (BDNF) is one of the most abundant neurotrophins in the adult brain, and it plays important roles in modulating synaptic plasticity and synaptogenesis. This study attempted to elucidate the role of the BDNF variant rs6265 in emotional symptoms following mild traumatic brain injury (mTBI).MethodsTo investigate the association between BDNF Val66Met polymorphism (rs6265) and emotional symptoms in mTBI patients, we recruited 192 mTBI patients and evaluated their Beck Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…More clinical data are emerging that estrogen may have no proconvulsant or even anticonvulsant effects, even though it is commonly accepted that estrogen affects neuronal excitability and thus may mediate pro-convulsant effects (Preux & Druet-Cabanac 2005). The pro-convulsant effect of estrogen has been linked to modulation of gene expression, direct interaction with neurotransmitter receptors and release and induction of brain derived neurotrophic factor (BNDF) which potentiates excitatory glutaminergic pathway in the hippocampus and elevation in seizure frequency, particularly after estradiol surge during periovulatory catamenial epilepsy (Scharfman & MacLusky 2006,Sohrabji et al 1995, Wang et al, 2018. However, estrogen also closely relate to endogenous molecules like NPY with seizure protecting property.…”
Section: Discussionmentioning
confidence: 99%
“…More clinical data are emerging that estrogen may have no proconvulsant or even anticonvulsant effects, even though it is commonly accepted that estrogen affects neuronal excitability and thus may mediate pro-convulsant effects (Preux & Druet-Cabanac 2005). The pro-convulsant effect of estrogen has been linked to modulation of gene expression, direct interaction with neurotransmitter receptors and release and induction of brain derived neurotrophic factor (BNDF) which potentiates excitatory glutaminergic pathway in the hippocampus and elevation in seizure frequency, particularly after estradiol surge during periovulatory catamenial epilepsy (Scharfman & MacLusky 2006,Sohrabji et al 1995, Wang et al, 2018. However, estrogen also closely relate to endogenous molecules like NPY with seizure protecting property.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tests of mood conducted at 1 and 6 weeks post-injury in another cohort of patients with mild TBI found more depression and anxiety in Met carriers. The effect on depression was modulated by gender, being significant at both time points in males but only at the first time point in females [57]. Mild TBI increased depressive rumination and reduced cognitive flexibility among Met carriers but not among Val/Val homozygotes.…”
Section: Val66met In Tbimentioning
confidence: 99%
“…The BDNFVal 66 Met polymorphism represents a substitution of valine to methionine in the BDNF pro-peptide, which decreases secretion of BDNF into the synapse (18). Recent studies have demonstrated that presence of the Met allele is associated with impaired cognition (21) and more emotional symptoms (22) in mild TBI patients.…”
Section: Introductionmentioning
confidence: 99%